Exploring Elements That Support Teachers Engagement in Online Professional Development - Sarah Prestridge; Jo Tondeur (MDPI AG, 2015)
This study sought to identify the most effective elements required in online professional development to enable teachers to improve their use of Information and Communications Technologies (ICT) in their classrooms. Four schools in Queensland were involved, with twelve classroom teachers participating in a year-long online professional development program over the school year supported by an online mentor. The online professional development program did not provide course based or sequential learning activities. Rather it was design to enable individual learning pathways and draw on the many professional learning opportunities available through web 2.0 tools and Internet resources. The focus was to explore the process of online ICT professional development to contribute to the conceptualization of how teachers learn in the 21st Century. Findings indicate that teachers need to engage in three elements: investigation, reflection, and constructive dialogue; build a sense of group and individual online presence; and be supported by mentorship that responds to the various cognitive and affective demands of autonomous learners.